Texture evolution and microcracking mechanisms in as-extruded and cross-rolled conditions of a 14YWT nanostructured ferritic alloy. (15th June 2018) - Pal, S.; Alam, M.E.; Maloy, S.A.; Hoelzer, D.T.; Odette, G.R.
Abstract: Cr-stabilized nanostructured ferritic alloys (NFAs), dispersion strengthened by an ultra-high density of nanooxides, are attractive candidates for many nuclear energy applications due to their high-temperature strength, in-service stability and remarkable irradiation tolerance. However, typical NFA deformation processing paths lead to crystallographic texturing, formation of brittle microstructures and low toughness orientations, making fabricating components very difficult. Here, we characterize the dislocation-mediated deformation mechanisms that lead to the brittle texture component. The as-extruded bar is less brittle than the cross-rolled plate, which contains a large population of pre-existing cleavage microcracks. More generally, deformed ODS/NFAs are most often textured and have anisotropic low toughness orientations, even absent microcracks. However, cross-rolling produces a very high volume fraction of a plate normal 001<110>-texture component, which constitutes the brittle cleavage system in iron. Microcracks propagate along 001 low angle deformation induced subgrain boundaries in <110> directions after nucleating by the Cottrell mechanism. Graphical abstract: Image 1